(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
Rust infected plant samples were collected during the periods from 2016 to 2020 from Tartous and Lattakia. Rust fungi species were identified on which Darluca filum(Biv.)Cast. hyperparasite on 18 different fungal species belonging to 5 different genera of rust fungi i.e., Puccinia, Uromyces, Phragmidium, Tranzschelia, and Melampsora. The higher frequency of parasitism viz. 100% was shown on the rust fungi infecting plant species belonging to the family Euphorbiaceae followed by family Poaceae76.47%, least of Asteraceae 33.33%. The severity of D.filum parasitism was counted as 900 Pycnidia / cm2 in Puccinia hordei Otth.. infecting Hordeum spontaneum K.Koch. and 3 Pycnadia /cm2 in Puccinia senecionis Lib. infecting Senecio vernalis Waldst.&Kit. The rate of infection of D.filum on the rust fungus P.hordei Otth. reached 75% on Hordeum spontaneum, while on P.senecionis infecting P.senecionis was 7.5%. This is the new record of the fungus D.filum in Syria on 12 species on Puccinia, one specie on Uromyces, 2 species on Tranzschelia, 2 species on Phragmidium, and one specie on Melampsora.